The Many Faces of the Flavivirus NS5 Protein in Antagonism of Type I Interferon Signaling - Best, Sonja M. (Journal of virology, 2017)
The vector-borne flaviviruses cause severe disease in humans on every inhabited continent on earth. Their transmission by arthropods, particularly mosquitoes, facilitates large emergence events such as witnessed with Zika virus (ZIKV) or West Nile virus in the Americas. Every vector-borne flavivirus examined thus far that causes disease in humans, from dengue virus to ZIKV, antagonizes the host type I interferon (IFN-I) response by preventing JAK-STAT signaling, suggesting that suppression of this pathway is an important determinant of infection. The most direct and potent viral inhibitor of this pathway is the nonstructural protein NS5. However, the mechanisms utilized by NS5 from different flaviviruses are often quite different, sometimes despite close evolutionary relationships between viruses. The varied mechanisms of NS5 as an IFN-I antagonist are also surprising given that the evolution of NS5 is restrained by the requirement to maintain function of two enzymatic activities critical for virus replication, the methyltransferase and RNA-dependent RNA polymerase. This review discusses the different strategies used by flavivirus NS5 to evade the antiviral effects of IFN-I and how this information can be used to better model disease and develop antiviral countermeasures.